Petonii Curiosa Felicitas: La función de las citas en el discurso de Eumolpo [Sat. 118] - Carmignani, Andrés (Centro de Estudios Latinos. IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2010)
This paper surveys the intertextual phenomenon of `quotation' in Petronius, Sat. 118, where the poet, Eumolpus, sets out his particular 'ars poetica'. In this speech, Eumolpus quotes the names of Homer, Virgil and Horace, along with Horace?s Carm. 3.1.1, which demonstrates that the poetaster bears in mind the Venusian author. The survey of the quotations in this passage is related to the fact that Petronius is an author who constantly alludes but rarely quotes, so that when he does it, the reader should pay close attention